2023
DOI: 10.1186/s12911-023-02366-2
|View full text |Cite
|
Sign up to set email alerts
|

Determining the content and needs assessment a mobile-based self-care program in infertile men

Azadeh Nadjarzadeh,
Alireza Fallahzadeh,
Arezoo Abasi
et al.

Abstract: Background Infertility is a public health problem in the world, using new technology, such as mobile phones, is increasing in the field of health. This study aimed to determine the Necessity of self-care training contents by performing a needs analysis among men with infertility problems to design a mobile phone-based application. Methods Followed by reviewing the related literature, a questionnaire including 40 educational items and seven software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Therefore, it can be concluded that the fear of birth is one of the main reasons for preferring cesarean section, especially among young and primiparous Iranian women. Rudsari et al‘s study showed that proper communication by midwives and doctors with pregnant women and providing childbirth advice to them reduces women’s fear and anxiety to perform birth and encourages them to perform birth [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the fear of birth is one of the main reasons for preferring cesarean section, especially among young and primiparous Iranian women. Rudsari et al‘s study showed that proper communication by midwives and doctors with pregnant women and providing childbirth advice to them reduces women’s fear and anxiety to perform birth and encourages them to perform birth [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A needs assessment is the process of collecting data to analyze differences between expected competence and actual competence. Then it is necessary to prioritize the differences (Tangdhanakanond & Wongwanich, 2012;Livergant et al, 2021;Nadjarzadeh et al, 2023). The need assessment process is divided into three parts, namely (a) identification of all the necessary needs that arise in the organization.…”
Section: Needs Assessmentmentioning
confidence: 99%